2002
DOI: 10.1046/j.1365-2125.2002.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of celecoxib by polymorphic cytochrome P450 2C9 and alcohol dehydrogenase

Abstract: Aims Celecoxib is a novel selective cyclooxygenase-2 inhibitor, which is subject to extensive hepatic metabolism. The aims of the present in vitro investigation were 1) to compare the rate of celecoxib hydroxylation by different genetic variants of cytochrome P450 2C9 (CYP2C9), and 2) to identify the enzyme(s) involved in the formation of the major metabolite carboxycelecoxib. Methods Hydroxycelecoxib formation was studied in human liver microsomes from 35 genotyped livers, as well as in yeast microsomes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 21 publications
4
76
0
1
Order By: Relevance
“…For example, the clearance of warfarin was recently shown to vary 12-fold in 54 patients homozygous for the CYP2C9*1 allele (Scordo et al, 2002). A similar variation in CYP2C9 enzyme activity has been demonstrated in human liver samples incubated with different CYP2C9 substrates in vitro (Yamazaki et al, 1998;Yasar et al, 2001b;Sandberg et al, 2002). Moreover, results from a study on patients treated with phenytoin showed that only 15% of the variation in dose-response could be explained by the *1-, *2-, or *3-polymorphisms of the CYP2C9 gene (Kerb et al, 2001).…”
mentioning
confidence: 85%
“…For example, the clearance of warfarin was recently shown to vary 12-fold in 54 patients homozygous for the CYP2C9*1 allele (Scordo et al, 2002). A similar variation in CYP2C9 enzyme activity has been demonstrated in human liver samples incubated with different CYP2C9 substrates in vitro (Yamazaki et al, 1998;Yasar et al, 2001b;Sandberg et al, 2002). Moreover, results from a study on patients treated with phenytoin showed that only 15% of the variation in dose-response could be explained by the *1-, *2-, or *3-polymorphisms of the CYP2C9 gene (Kerb et al, 2001).…”
mentioning
confidence: 85%
“…Chemical structure of CEL is 4-[5-(4-methylphenyl)-3-(trifluoromethyl)-1H-pyrazole-1-yl] benzenesulfonamide ( Manzoori et al, 2005) as shown in Figure 1. Metabolism of CEL takes place in liver by the enzymes cytochrome P450 2C9 (Cyp 2C9) (Sandberg et al, 2002;Sweetman et al, 2007), a cytochrome P450 isoform that is known to exist as several genetic variants (Stormer et al, 2003). CEL eliminated primarily by metabolism and about 3% is recovered in urine and faeces as unchanged compound (Stempak et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…25 An in vitro study utilizing human liver microsomes in addition to yeast microsomes expressing a number of CYP polymorphisms showed that CYP2C9*3 had a lower intrinsic clearance of celecoxib when compared with the wild-type CYP2C9*1 samples. 26 There are conflicting results about whether CYP2C9*2 has a significant decrease in intrinsic clearance. 26,27 The most marked decrease in metabolism of celecoxib was noted in enzymes expressing homozygous polymorphism CYP2C9*3/*3.…”
Section: Diaryl Heterocyclic Cox-2-selective Inhibitorsmentioning
confidence: 99%
“…26 There are conflicting results about whether CYP2C9*2 has a significant decrease in intrinsic clearance. 26,27 The most marked decrease in metabolism of celecoxib was noted in enzymes expressing homozygous polymorphism CYP2C9*3/*3. 26,27 A corresponding increase in celecoxib's AUC would be expected in individuals expressing CYP2C9*3 allele, and this could result in an increase in dose-related adverse reactions due to accumulation of celecoxib.…”
Section: Diaryl Heterocyclic Cox-2-selective Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation